A DNA Methyltransferase Inhibitor, 5‐Aza‐2′‐Deoxycytidine, Exacerbates Neurotoxicity and Upregulates Parkinson's Disease‐Related Genes in Dopaminergic Neurons. (26th February 2013) - Wang, Yong; Wang, Xuan; Li, Ran; Yang, Zhao‐Fei; Wang, Yi‐Zheng; Gong, Xiao‐Li; Wang, Xiao‐Min
Summary Aims To investigate effects of DNA methyltransferase (DNMT) inhibitors on dopaminergic neurons and its underlied mechanism. Methods The DNMT inhibitor 5‐aza‐2′‐deoxycytidine (5‐aza‐dC) was tested in cultured dopaminergic cells. Cell viability and apoptosis were assayed with 5‐aza‐dC alone. Neurotoxicity of 1‐methyl‐4‐phenylpyridinium (MPP+), 6‐hydroxydopamine or rotenone was also assayed with 5‐aza‐dC pretreatment. And mRNA levels of several key PD‐related genes were examined by semiquantitative RT‐PCR. Furthermore, CpG methylation of α‐synuclein promoter was examined by bisulfite sequencing. Results 5‐aza‐dC resulted in decreased cell viability and increased apoptosis in dopaminergic neuronal cells. Pretreatment with 5‐aza‐dC exacerbated neurotoxic damage to dopaminergic neurons induced by MPP+, 6‐hydroxydopamine or rotenone. 5‐aza‐dC also induced transcriptional upregulation of the key PD‐related genes tyrosine hydroxylase and α‐synuclein. And demethylation of CpG in α‐synuclein promoter was also induced by 5‐aza‐dC and MPP+. Conclusions This DNMT inhibitor might influence pathogenesis of PD. And demethylation induced by DNMT inhibitor might contribute to dopaminergic neuron death, by increasing vulnerability of dopaminergic neurons to neurotoxins and by misregulating transcription of key PD‐related genes. Our data also suggested DNMT inhibitors may cause multiple effects on dopaminergic neurons.